Assessment of Senior Secondary School Students' Knowledge of Nutritional Practices in Delta State, Nigeria - Oghenevwarhe Itagar (Lembaga Riset Mutiara Akbar, 2025)
This study assessed the knowledge of nutritional practices among Senior Secondary School students in Delta State, Nigeria. An ex-post facto research design and descriptive survey method were adopted. A sample of 390 students was selected from a population of 14,819 using Slovin’s formula and multi-stage sampling techniques. Data were collected through a validated questionnaire with a reliability coefficient of 0.81 and analyzed using mean, standard deviation, and t-test statistics at a 0.05 significance level. The findings revealed that students possessed a high level of nutritional knowledge, with mean scores ranging from 2.78 to 3.28, indicating strong awareness of healthy dietary practices and the importance of Food and Nutrition education. The study also found a significant difference between urban and rural students’ nutritional knowledge (t = 35.15, p < 0.05), suggesting that location influences access to nutrition-related information. The study concludes that nutrition knowledge among students is generally high, although efforts are needed to address urban–rural disparities.